Body Size Predicts Cardiac and Vascular Resistance Effects on Men's and Women's Blood Pressure - Evans, Joyce M.; Wang, Siqi; Greb, Christopher; Kostas, Vladimir; Knapp, Charles F.; Zhang, Qingguang; Roemmele, Eric S.; Stenger, Michael B.; Randall, David C. (Frontiers in Physiology, 2017)
Effects of body size on inter-subject blood pressure (BP) variability are not well established in adults. We hypothesized that relationships linking stroke volume (SV), cardiac output (CO) and total peripheral resistance (TPR) with body size would account for a significant fraction of inter-subject BP variability. Methods Thirty-four young, healthy adults (19 men, 15 women) participated in 38 stand tests during which brachial artery BP, heart rate, SV, CO, TPR and indexes of body size were measured/calculated. Results Steady state diastolic arterial BP was not significantly correlated with any index of body size when subjects were supine. Upon standing, the more the subject weighed, or the taller s/he was, the greater the increase in diastolic pressure. Systolic pressure strongly correlated with body weight and height both supine and standing. Diastolic and systolic BP were more strongly related to height, weight and body surface area than to body mass index. When supine: lack of correlation between diastolic pressure and body size, resulted from the combination of positive SV correlation and negative TPR correlation with body size. The positive systolic pressure vs body size relationship resulted from a positive SV vs height relationship. In response to standing: the positive diastolic blood pressure vs body size relationship resulted from the standing-induced, positive increase in TPR vs body size relationship. The relationships between body weight or height with SV and TPR contribute new insight into mechanisms of BP regulation that may aid in the prediction of health in young adults by providing a more effective way to scale BP with body size.